Trends in prescription opioid use in Europe: A DARWIN EU® multinational cohort study including seven European countries - Xie, Junqing; Du, Mike; Guo, Yuchen; Barboza, Cesar; Brash, James T.; Delmestri, Antonella; Duarte-Salles, Talita; Gratton, Jasmine; Griffier, Romain; Kolde, Raivo; Man, Wai Yi; Mercadé-Besora, Núria; et al. (Frontiers in Pharmacology, 2025)
BackgroundThe opioid crisis has been a serious public health challenge in North America for decades, despite numerous efforts to mitigate its devastating consequences. As concerns grow about a similar situation developing in Europe, we evaluated the trends in opioid use and characterized prescribing indications across seven European countries.MethodsWe conducted a multinational cohort study using electronic health records from various healthcare settings: primary care [Clinical Practice Research Datalink (CPRD) GOLD (United Kingdom), Sistema d’Informació per al Desenvolupament de la Investigació en Atenció Primària (SIDIAP, Spain), and Integrated Primary Care Information Project (IPCI, the Netherlands)]; primary and outpatient specialist care [IQVIA Disease Analyzer (DA) Germany and IQVIA Longitudinal Patient Database (LPD) Belgium]; hospital care [Clinical Data Warehouse of Bordeaux University Hospital (CHUBX, France)]; and the Estonian Biobank (EBB). All data were mapped to the Observational Medical Outcomes Partnership (OMOP) Common Data Model (CDM). All people registered in a contributing database for ≥365 days between 2012 and 2022 were included. Annual period prevalence and incidence rates of opioid prescriptions were estimated, and long-term trends were quantified as the percent change from 2012 to 2019. New opioid users were characterized, including potential prescribing indications.ResultsBetween 2012 and 2019, the incidence of opioid prescriptions in primary care decreased by −50·7% (CPRD GOLD) and −2·0% (SIDIAP), while it increased in EBB (+52·8%) and CHUBX (+25·3%) data. The incidence of codeine and tramadol use decreased in most databases. However, the prevalence of oxycodone, morphine, and fentanyl increased. Opioid use was highest among older age groups, and the majority of prescriptions were for oral formulations. Respiratory and pain-related conditions were the most common indications for new opioid users in outpatient settings.ConclusionDespite a decrease in new opioid prescriptions in many European countries, the prevalence of opioid use remained largely stable over the last decade. More data are needed to monitor evolving opioid prescription patterns in Europe, particularly in the post-pandemic era.